Implementation of E-Government by the Batang Regency Government in Supporting Village Governance in Batang Regency - ST. Amri Alimatul Muflikhah; Tri Lestari Hadiati; Karmanis Karmanis (International Journal of Sociology and Law, 2026)
Digital transformation of government through the implementation of e-government has become a strategic agenda in bureaucratic reform in Indonesia. Local governments play a crucial role as a bridge between national policies and village governance practices. This article analyzes the implementation of e-government by the Batang Regency Government in support of village governance. This research uses a qualitative approach and a policy analysis method, based on literature reviews and official documents, including regional regulations, SPBE policies, and relevant institutional reports. The analysis was conducted using a theoretical framework of public policy implementation and the principles of good governance. The analysis results indicate that the Batang Regency Government has a relatively adequate e-government regulatory and institutional framework, but its implementation at the village level still faces challenges, including gaps in apparatus capacity, variations in village digital readiness, and suboptimal cross-organizational coordination. This article concludes that strengthening the role of local governments as facilitators, coaches, and coordinators of digital policies is key to the successful implementation of village e-government. These findings provide theoretical contributions to e-government studies and policy implementation, as well as practical implications for formulating local government digital policies.